Risk Factors for the Failure of Epidural Labor Analgesia Conversion to Cesarean Section Anesthesia and the Incidence of General Anesthesia: Systematic Review - Angelita; Jimmy (The International Journal of Medical Science and Health Research, 2024)
Background: Epidural analgesia has become pivotal in modern obstetric care for managing labor pain, yet a notable percentage of recipients (4-14%) may require a cesarean section, prompting the need for effective epidural-to-surgical anesthesia conversion. This review aims to minimize the use of general anesthesia, which carries inherent risks and is discouraged in favor of safer alternatives like spinal or epidural anesthesia according to international guidelines. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines.The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Conclusion: Challenges with inadequate neuraxial anesthesia in elective cesarean sections underscore the need for optimized surgical conditions and pain relief strategies, while the conversion of labor epidural analgesia to anesthesia for emergency cesarean sections emphasizes the critical factors of anesthetic efficacy and procedural success rates in obstetric care.